IMPLEMENTASI PROGRAM MICRO TEACHINGBAGI GURU BAHASA ARAB DI PESANTREN AR-RAUDHATUL HASANAH MEDAN - Imam Tazali (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: The purpose of this study was to determine the application of learning Arabic languagesapport using micro teaching program on learning the Arabic language the application of microteaching program in Arabic language learning aimed to the ability of Arabic teacher in Islamic BoardingSchool Ar-Raudhatul Hasanah Medan in the Arabic language support. This research is using thequalitative method. The technique for this data collection is using interview, documentation andobservation, analysis data technique is using data reduction, data available and taking a summary.The checking of valid data is using triangulation, reference data and the writer’s attention. Thisresearch is located at Ar-Raudhatul Hasanah Islamic Boarding School. The time of research is startedfrom March to October 2016. The research concludes that the implementation of micro teachingprogram for Arabic language teacher in Islamic boarding school Ar-raudhatul Hasanah is planningbased on the concept plan include formulating learning goals. This program to increase the competencyArabic language for Islamic pupil in the learnig process and impraving the ability of student tounderstand the material contained within each core discussion of Arabic language teacher preparation,class preparation, measure of student learning activities and evaluation learning. The application ofthis methods is conversation learning tools, speech, discussion and writing. In this activity usinginterviews and testing program with the audio target that is expected the and of the activities isassessed with decription maturity of learning Arabic language. The teacher capacity or ability ofArabic language is to caltivate the spirit of love for the Arabic teacher improving quality and providethe positive effects and give the comprehensive and developed the teaching concept.Kata kunci: Micro Teaching, Bahasa Arab, Pesantren